Visits for Medically Unspecified Disease in General Internal Medicine Clinics of County General Hospitals - LOU Zheng, LIU Ying, REN Jingjing (Zhongguo quanke yixue, 2023)
Background Medically unspecified disease (MUD) is characterized by complex and diverse symptoms that cannot be clearly diagnosed or rationally explained, which often leads to frequent hospital attendance, imposing a heavy economic burden on individuals, families and the healthcare system. Objective To understand the visits for MUD in general internal medicine clinics in county general hospitals by analyzing the results of a survey, providing a theoretical basis for standardized treatment of MUD by integrating evidence from this epidemiological survey and our ideas for general diagnosis and treatment of MUD in county general hospitals. Methods From January to March 2021, conditional sampling was used to select all patients (n=45 439) who attended the general internal medicine clinic (85 881 visits in total) in a grade B tertiary county general hospital in Taizhou, Zhejiang Province from January 1 to December 31, 2020 through the hospital information system. Among whom, adult patients with MUD were screened using the PRESUME screening method, and information involving the demographics, time of consultation and reasons for consultation was collected for analysis. Results A total of 497 adult patients were identified with visits due to MUD, with a mean number of visits of 2.23 visits/person, and a mean age at visit of (51.6±15.9) years. There were sex-specific differences in age composition and attendances of MUD patients (P<0.01). As for the reasons for visits, men had more visits due to anxiety than women (P<0.05). The visits due to abdominal pain, anxiety and cough differed significantly by age (P<0.05). The visits in different seasons showed no significant differences by sex and age (P>0.05). The visits for cough differed significantly across the seasons (P<0.05) . Conclusion According to this survey, the visits due to MUD are influenced by various factors such as gender, age and season. Frequent visits for MUD due to various reasons cause difficulties in identifying and rationally treating the disease in the general internal medicine clinic as the first contact setting. To provide more accurate diagnosis and treatment for MUD patients, it is necessary to further develop the general medicine department, and make the general medicine department in county hospitals become the primary care center for MUD, and comprehensively enhance the effectiveness of county hospitals in serving the society.